Norbornadiene‐Based Photoswitches with Exceptional Combination of Solar Spectrum Match and Long‐Term Energy Storage. Issue 49 (16th August 2018) - Jevric, Martyn; Petersen, Anne U.; Mansø, Mads; Kumar Singh, Sandeep; Wang, Zhihang; Dreos, Ambra; Sumby, Christopher; Nielsen, Mogens Brøndsted; Börjesson, Karl; Erhart, Paul; Moth‐Poulsen, Kasper
Abstract: Norbornadiene‐quadricyclane (NBD‐QC) photoswitches are candidates for applications in solar thermal energy storage. Functionally, they rely on an intramolecular [2+2] cycloaddition reaction, which couples the S0 landscape on the NBD side to the S1 landscape on the QC side of the reaction and vice‐versa. This commonly results in an unfavourable correlation between the first absorption maximum and the barrier for thermal back‐conversion. This work demonstrates that this correlation can be counteracted by using steric repulsion to hamper the rotational motion of the side groups along the back‐conversion path. It is shown that this modification reduces the correlation between the effective back‐conversion barrier and the first absorption maximum and also increases the back‐conversion entropy. The resulting molecules exhibit exceptionally long half‐lives for their metastable forms without significantly affecting other properties, most notably solar spectrum match and storage density. Abstract : A series of 2‐cyano‐3‐aryl norbornadienes were synthesized and the properties studied for molecular solar thermal (MOST) energy storage. The quadricyclane isomers with substituents in the ortho ‐position exhibited exceptionally high thermal stability without compromising the other properties. Calculations show a greatly enhanced barrier of rotation in the quadricyclane form coming about from this steric congestion interfering with the transition state.